2019
DOI: 10.3389/fneur.2019.00701
|View full text |Cite
|
Sign up to set email alerts
|

Immune Profile in Blood Following Non-convulsive Epileptic Seizures in Rats

Abstract: Non-convulsive status epilepticus (NCSE) is a prolonged epileptic seizure with subtle symptoms that may delay clinical diagnosis. Emerging experimental evidence shows brain pathology and epilepsy development following NCSE. New diagnostic/prognostic tools are therefore needed for earlier and better stratification of treatment. Here we examined whether NCSE initiates a peripheral immune response in blood serum from rats that experienced electrically-induced NCSE. ELISA analysis showed an acute transient increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…KC/GRO levels were, however, not significantly increased during control conditions, suggesting that the blocking of the release of KC/GRO via P2X7R is restricted to pathological conditions (i.e., status epilepticus, epilepsy) when high amounts of extracellular ATP are available to activate the P2X7R [ 61 ]. In contrast to our studies which showed no differences in KC/GRO levels between control conditions and status epilepticus/epilepsy in plasma, previous data have shown increased KC/GRO protein levels in the hippocampus of rats 12 h post-status epilepticus [ 62 ], in the brain and in plasma of rats with non-convulsive status epilepticus [ 63 ], and in the CSF of pediatric patients with febrile infection-related epilepsy syndrome [ 64 ]. Differences in models used, timing of sampling post-status epilepticus, or tissue may account for these observed differences between studies, which should be addressed in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…KC/GRO levels were, however, not significantly increased during control conditions, suggesting that the blocking of the release of KC/GRO via P2X7R is restricted to pathological conditions (i.e., status epilepticus, epilepsy) when high amounts of extracellular ATP are available to activate the P2X7R [ 61 ]. In contrast to our studies which showed no differences in KC/GRO levels between control conditions and status epilepticus/epilepsy in plasma, previous data have shown increased KC/GRO protein levels in the hippocampus of rats 12 h post-status epilepticus [ 62 ], in the brain and in plasma of rats with non-convulsive status epilepticus [ 63 ], and in the CSF of pediatric patients with febrile infection-related epilepsy syndrome [ 64 ]. Differences in models used, timing of sampling post-status epilepticus, or tissue may account for these observed differences between studies, which should be addressed in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…The signs of neuroinflamma tion following LPS administration were also maintained for a long time. Analysis of the microglia response to the intra hippocampal infusion of LPS (10 μg) showed an increased number of activated microglial cells at all times (6 and 24 h, 1 and 4 weeks) after endotoxin administra tion [76].…”
Section: Activation Of Neuroinflammation As a Potential Factor In The Long Term Genes Induction In The Hippocampusmentioning
confidence: 97%
“…Silverberg et al utilized extracranially placed electrodes to potentiate seizures in mice, and they observed peripheral lymphocytes (including Th cells) infiltration into the brain 24 h after a maximal seizure, which peaked at 48 h and became undetectable at 7 d ( 234). Avdic et al utilized intracranial electrode to induce non-convulsive status epileptics, a prolonged epileptic seizure with subtle symptoms, in rats (265). They reported increased levels of IL-6 in both brain and serum 6 h after non-convulsive epileptic seizures, and after 4 weeks when 75% of those rats exhibited spontaneous seizures (SS), they further compared those rats with SS to both those without and unstimulated rats, finding a decrease of CD4 + T cells in the peripheral blood.…”
Section: Epilepsymentioning
confidence: 99%